La filosofía política y del derecho a luz del pensamiento de Santo Tomás de Aquino (2019)
The present article pretends to glimpse the "political and legal philosophy" of our patron, St. Thomas Aquino. Thus, emphasizing, the materialization of the plexus of values inculcated and promulgated by the State, under the interests of the inclusion of the "other", that is, to serve the collective good as "political animals" that we are and only Established by justice. The above remembering that Thomas Aquino is a current thinking, because:   "Thomistic philosophy is a perennial philosophy, that is, to refer to that transsectal philosophy that always comes back and comes into contact with the new problems of each epoch and that is not displaced or definitively replaced by another (...) it is not only a historical reality, because it possesses a universal substance that surpasses the fashions of all times, although, without a doubt, it must cover in each  restoration new problematizations or new languages "(Cárdenas Sierra & Guarín Ramírez, 2006, p.94 ). ) (External cursive text).